PENDEKATAN SEMANTIK TOSHIHIKO IZUTSU: KONSEPSI AGAMA (DIN) SEBAGAI KEPATUHAN - Arya Chandra Argadinata; Hudaeva, Andi Rosa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study analyzes Toshihiko Izutsu's semantic approach in understanding the concept of "din" (religion) in the Qur'an. With an integrated linguistic method, Izutsu highlights the meaning of words through synchronous and diachronic perspectives, and makes use of modern and traditional theories. He revealed that "din" in the Qur'an has two main semantic values, namely obedience (ta'ah) and servitude ('ubudiyah), and shows the relevance of transforming its meaning in social and cultural contexts. This study also compares Izutsu's views with other figures such as Buya Hamka, Quraish Shihab, and al-Attas to explore the variation in the meaning of the term "din". Despite the criticism, Izutsu's semantic approach is still recognized as making a significant contribution in opening up new insights into the study of the Qur'an, including in the fields of Islamic ethics and philosophy. This study seeks to describe the uniqueness of Izutsu's interpretive method as an integrative interpretation that combines various contexts of the meaning of the Qur'an in a modern framework